Nickel coins from 1925 - Pantelić Svetlana (Bankarstvo, 2018)
The Minister of Finance, Dr Milan Stojadinović, signed a contract on the production and delivery of 1/2-, 1- and 2-dinar nickel coins on 30 December 1924. The French Minting Association from Paris undertook the delivery of these coins with a nominal value of 200 million dinars and a weight of 1000 tonnes, together with their partner, the Belgian Royal Mint from Brussels. Half of these coins were minted in France, while the rest is assumed to have been minted in Brussels or Belgrade. On 5 September 1925, the National Bank released all three denominations in batches, as they arrived from the mint. That year, in nominal terms, that amounted to 92,765,850 dinars and in 1926 to 71,846,450 dinars. There were more of these coins amounting to 35,387,700 dinars in the treasuries of the National Bank, serving as a depot of the Ministry of Finance. The 2-dinar and 1/2-dinar coins were being withdrawn from circulation from 16 August 1939 to 16 August 1940, and the 1-dinar coins were being withdrawn from 20 October 1939 to 20 April 1940.